The power of fantasy : modern and contemporary art from Poland - Crowley, David; Bozar - Paleis voor Schone Kunsten, Brussel; Machnicka, Zofia; Szczerski, Andrzej (New York, NY : Prestel, 2011)
Introduction: The power of fantasy / David Crowley, Zofia Machnicka and Andrzej Szczerski ##Essays: The Polish art of mnemonics / Andrzej Szczerski ; Micromegas, or Playing with architecture in contemporary Polish art / Gabriela Świtek ; Sacrifice, madness, ruins and other Polish dreams / David Crowley ##Artists: Paweł Althamer ; Wojciech Ba̜kowski ; Mirosław Bałka ; Cezary Bodzianowski ; Olaf Brzeski ; Anna Janczyszyn-Jaros ; Katarzyna Józefowicz ; Szymon Kobylarz ; Jarosław Kozakiewicz ; Katarzyna Kozyra ; Igor Krenz ; Zofia Kulik ; Maciej Kurak ; Robert Kuśmirowski ; Zbigniew Libera ; Marcin Maciejowski ; Paulina Ołowska ; Włodzimierz Pawlak ; Józef Robakowski ; Zbigniew Rybczyński ; Wilhelm Sasnal ; Janek Simon ; Monika Sosnowska ; Mariusz Waras ; Julita Wójcik ; Jakub Julian Ziółkowski ; Artur Z̊mijewski / biographical profiles written by Karol Sienkiewicz.
This catalogue is published on the occasion of the exhibition 'The Power of Fantasy - Modern and Contemporary Art from Poland', Centre for Fine Arts, Brussels, 24.06-18.09.2011
boek